Proceedings of the Golden Age of Cataclysmic Variables and Related Objects v — PoS(GOLDEN2019) 2021
DOI: 10.22323/1.368.0013
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Cataclysmic Variables in Globular Clusters

Abstract: The study of star clusters plays an important role in our understanding of the Universe since these systems are natural laboratories for testing theories of stellar dynamics and evolution. Particularly, globular clusters (GCs) are one of the most important objects for studying the formation and the physical nature of exotic systems which in turn provide basic information and tools that can help us to understand the formation and evolution processes of star clusters themselves, galaxies and, in general, the you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…measurements that are less precise due to some distant clusters or clusters with a limited number of X-ray sources included in their sample (see Heinke et al 2020;Belloni & Rivera Sandoval 2021, for a deeper discussion on this), it is important to note that in Pooley & Hut (2006), there might be a bias due to small number statistics, which is important to consider when interpreting their correlation with γ.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…measurements that are less precise due to some distant clusters or clusters with a limited number of X-ray sources included in their sample (see Heinke et al 2020;Belloni & Rivera Sandoval 2021, for a deeper discussion on this), it is important to note that in Pooley & Hut (2006), there might be a bias due to small number statistics, which is important to consider when interpreting their correlation with γ.…”
Section: Resultsmentioning
confidence: 99%
“…Due to crowding, the identification of CVs in globular clusters (GCs) is challenging. Yet, they have been confirmed spectroscopically and mainly studied photometrically in several Galactic GCs (for a review of CVs in GCs, see Belloni & Rivera Sandoval 2021).…”
Section: Introductionmentioning
confidence: 99%
“…None of them are close to the detected astrometric binaries. In globular clusters, the typical X-ray sources are cataclysmic variables (Belloni & Rivera 2021). They are relatively tight binaries composed of a white dwarf or a neutron star and a main-sequence star as donor.…”
Section: Discussion and Future Studiesmentioning
confidence: 99%
“…Due to stellar interactions and their primordial formation, several of them are thought to be in cataclysmic variables. While many cataclysmic variables are expected to be in the cores of clusters due to mass segregation, around 50% of the predicted detectable cataclysmic variables are believed to be outside the half-light radus, particularly in those globular clusters with half-mass relaxation times longer than a few Gyr (see Belloni & Rivera Sandoval 2021, for a review on cataclysmic variables in globular clusters). The wide-field coverage and 10 yr duration of Rubin LSST will allow to us identify dwarf novae in the outskirts of globular clusters through their outbursts.…”
Section: (B) Identification Of Dwarf Novaementioning
confidence: 99%
“…Photometry in multiple filters will be helpful to corroborate variability detection and to place the identified systems in the color-magnitude diagram of the host cluster. This will be useful to further investigate the two-population problem of cataclysmic variables in globular clusters (e.g., Cohn et al 2010;Belloni & Rivera Sandoval 2021) (c) Characterization of exotic binaries and pulsating stars Recent studies have shown the presence of several X-ray sources in the outer parts of globular clusters, which indicates binary interactions. Therefore, besides detecting accreting white dwarfs, the 10 yr duration and multicolor photometry of Rubin LSST will help to characterize binaries with neutron stars or even black holes.…”
Section: (B) Identification Of Dwarf Novaementioning
confidence: 99%